Ketika Lean Tidak Hanya Mengenai Efisiensi: Efektivitas Lean pada Badan Usaha Berbasis Layanan Konsumen - Widjaja, Gresyelda Lavinia; Pontjoharyo, Wiyono (Jurnal Riset Akuntansi dan Keuangan, 2021)
Lean principle has been commonly used in the manufacturing industry, but as the time goes by, the service industry has also begun to adapt this principle. Lean principles in the service industry, particularly in finance and accounting, can improve quality, timeliness, and overall value delivered by simplify processes and reduce non value added activities, or known as lean accounting services. Lean principle is commonly related to efficiency, whereas every business entity also has their long-term goals to be achieved. This exploratory research focuses on the phenomena that exist in the disbursement department at PT G through their activities specifically in delivering accounting service based on lean principles. By using a qualitative interpretation method, this study aims to explore how business entity not only increases efficiency, but can also be effective in achieving their goals. This research reveals that customer service based company can also takes the advantage from the adoption of Kaizen principle throughout Kaizen tools while developing the continuous improvement mindset. PT G improves their operational efficiency while fulfilling the customer expectation and company goals. This success is also affected by the management team support and relevant company value.